(untitled) (Scientia Agricola, 2016)
Processes regulating pesticide fate in the environment are influenced by the physicochemical properties of pesticides and soils. Sorption and desorption are important processes as they regulate the movement of pesticides in soil. Although sorption-desorption is widely studied for herbicides, studies involving their metabolites in soil are scarce. Sorption and desorption of indaziflam metabolites (indaziflam-triazinediamine (FDAT), indaziflam-triazine-indanone (ITI) and indaziflam-carboxilic acid (ICA)) were investigated in six Brazilian (BRA) soils and three United States (USA) soils with different physicochemical properties. The Freundlich equation described sorption of the metabolites for all soils (R2 >; 0.98; 1/n 1). Sorption order (Kf) was ITI >; ICA >; FDAT. Mean values of Kf,oc were 453, 289, and 81 (BRA) and 444, 48, and 48 (USA) for metabolites ITI, ICA, and FDAT respectively. Desorption was hysteretic for all metabolites in all soils. These results suggest that these metabolites fall in the classification range of mobile to moderately mobile in soils.